GAMBARAN SIKAP REMAJA AWAL TERHADAP IKLAN ANTI ROKOK - Freeco Lisa Lamhab Sari (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
ABSTRACT Development of the cigarette industry in Indonesia in recent years has increased. According in data from the World Institute for Health Care (WHO), the member of smokers in Indonesia is ranked third in the world, while for the ASEAN region, Indonesia tops the list, The death rate from smoking in Indonesia reaches 427.948 people annually, most of them are of productive age. The purpose of this study was to determine Preview Early Adolescent Attitudes toward Anti Smoking Advertising. The research was conducted by quantitative descriptive methode. Study was conducted on 56 people arl teens, who sit in second grade junior high school. Engineering samples used was quota sampling. Prior to data analysis, first testing the validity and reliability of research instrument with SPSS. The result showed that of three components of attitudes toward advertising, the affective component, cognitive component, and conative components, describing all aspects of early adolescent attitudes toward antismoking ads. Keywords: Early Adolescent, Anti Smoking Advertisment